Toxicology in the Middle Ages and Renaissance (Elsevier/Academic Press, 2021)
Toxicology in the Middle Ages and Renaissance provides an authoritative and fascinating exploration into the use of toxins and poisons in the Middle Ages and Renaissance. Part of the History of Toxicology and Environmental Health series, this volume is a follow-up, chronologically, to the first two volumes which explored toxicology in antiquity.